Significados do trabalho atribuídos por mulheres egressas de engenharia civil de uma universidade tecnológica - Manske, Luisa Pereira (2021)
Civil Engineering stands out among the technological areas that most graduate students in the country. The profession has a socially constructed status and a long history of male presence, with the work of women marked by the sexual division of labor. This dissertation was constructed based on the Marxist conception of work and the definition of the sexual division of labour, as well as the concept of meaning of Cultural-Historical Theory. It also used authors from the field of Science, Technology and Society to understand the relationship between society and the technological area ofengineering. The objective was to analyze the meanings of work attributed by women graduated from the Civil Engineering major at a public technological university in Curitiba. Among the specific objectives, we sought to identify the historical meanings of the general context of women in engineering in the literature and to understand the meanings of engineering education of the graduates interviewed, as well as the meanings of work attributed by them as women graduating in this major. Qualitative research sought to meet its objectives through a methodology based on the Qualitative Epistemology proposed by Fernando González Rey, which guided the methodology for collecting and analyzing information. The study was carried out with six graduated women from the Civil Engineering major of the Federal University of Technology – Paraná (UTFPR) from 2013 to 2018 and, as a research instrument, semi-structured interview with the participants were used, whose contacts were raised through the Snowball Technique. As a result, it is possible to verify that the meanings of power and status linked to engineering were fundamental to its elite character and masculinization of this professional field. The engineering degree keeps the meaning of a difficult course and the work in internships was of great importance for the interviewees. During the period they were in graduation, the instabilities of the civil construction market made them review and reconstruct the meaning they had about Civil Engineering as a prestigious career. The interviewees were widely encouraged by the family to pursue this profession and lived with many women during their undergraduate studies, pointing to a change in the male meaning of education in Civil Engineering. However, the entry of these women into the profession continues to be surrounded by episodes of discrimination and harassment that indicate a continuation of the sexual division of labour in engineering. The interviewees, however, have an awareness of these practices, questioning them and acting in a way to transform their workplaces. There is also a questioning of what it means to be an engineer today and a process of building their professional identities.